The proteasome inhibitior bortezomib depletes plasma cells and ameliorates clinical manifestations of refractory systemic lupus erythematosus. Issue 7 (20th February 2015) - Alexander, Tobias; Sarfert, Ramona; Klotsche, Jens; Kühl, Anja A; Rubbert-Roth, Andrea; Lorenz, Hannes-Martin; Rech, Jürgen; Hoyer, Bimba F; Cheng, Qingyu; Waka, Aderajew; Taddeo, Adriano; Wiesener, Michael; et al.
Abstract : Objectives: To investigate whether bortezomib, a proteasome inhibitor approved for treatment of multiple myeloma, induces clinically relevant plasma cell (PC) depletion in patients with active, refractory systemic lupus erythematosus (SLE). Methods: Twelve patients received a median of two (range 1–4) 21-day cycles of intravenous bortezomib (1.3 mg/m 2 ) with the coadministration of dexamethasone (20 mg) for active SLE. Disease activity was assessed using the SLEDAI-2K score. Serum concentrations of anti–double-stranded DNA (anti-dsDNA) and vaccine-induced protective antibodies were monitored. Flow cytometry was performed to analyse peripheral blood B-cells, PCs and Siglec-1 expression on monocytes as surrogate marker for type-I interferon (IFN) activity. Results: Upon proteasome inhibition, disease activity significantly declined and remained stable for 6 months on maintenance therapies. Nineteen treatment-emergent adverse events occurred and, although mostly mild to moderate, resulted in treatment discontinuation in seven patients. Serum antibody levels significantly declined, with greater reductions in anti-dsDNA (∼60%) than vaccine-induced protective antibody titres (∼30%). Bortezomib significantly reduced the numbers of peripheral blood and bone marrow PCs (∼50%), but their numbers increased between cycles. Siglec-1 expression on monocytes significantly declined. Conclusions: These findings identify proteasome inhibitors as a putative therapeutic option for patients with refractory SLE by targeting PCs and type-I IFN activity, but our results must be confirmed in controlled trials.